PENGATURAN KAMPANYE PILKADA SEBAGAI SARANA PENDIDIKAN POLITIK - Gunawan Arifin; Saharuddin Djohas; Irzha Friskanov. S (Riau Law Journal, 2023)
AbstractIn principle, regional elections are a means of implementing the people in the area in order to realize people's welfare. Therefore, regional election arrangements are designed not only as a mechanism for changing regional leaders but also as a means of increasing the political education of the people so that they can build local democracy with integrity. The problem is that the current election campaign arrangements can encourage an increase in people's political education as well as the concept of an ideal campaign arrangement as a means of political education using empirical juridical research methods. The current campaign settings are not optimal for providing reinforcement for increasing public political education. At the campaign stage, people who have voting rights receive information regarding the candidate's vision and mission and guarantee the autonomous participation of the community. Strengthening campaign materials that are oriented towards increasing political awareness of the people should be carried out, which can support the realization of local democracy with integrity, as well as optimizing the functions of the KPUD in improving political community education.AbstrakPada prinsipnya pemilihan kepala daerah (pilkada) adalah sarana pelaksanaan kedaulatan rakyat di di daerah guna mewujudkan kesejahteraan masyarakat. Oleh karena itu pengaturan pilkada didesain bukan hanya sebagai mekanisme pergantian pemimpin daerah semata.  Namun menjadi sarana dalam meningkatkan pendidikan politik masyarakat sehingga dapat membangun demokrasi lokal yang berintegritas. Permasalahannya adalah pengaturan kampanye pilkada saat ini dapat mendorong peningkatan pendidikan politik masyarakat serta konsep ideal pengaturan kampanye sebagai sarana pendidikan politik dengan menggunakan metode penelitian yuridis empiris. Pengaturan kampanye saat ini kurang optimal dalam memberikan penguatan dalam peningkatan pendidikan politik masyarakat. Pada tahapan kampanye, masyarakat yang memiliki hak suara hendaknya mendapat infomasi terkait visi misi kandidat serta menjamin partisipasi otonom masyarakat. Hendaknya dilakukan penguatan materi kampanye yang beriorientasi pada peningkatan kesadaran politik masyarakat yang dapat mendukung terwujudnya demokrasi lokal yang berintegritas, serta optimalisasi fungsi KPUD dalam meningkatkan pendidikan politik masyarakat.